PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE TEAM GAMES TOURNAMENT DI KELAS IV SD NEGERI 15 ULU GADUT KOTA PADANG - Ikhsan, Ikhsan; Yesi Anita; Fikhen Tri Wulandari; Reinita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the improvement of student learning outcomes in Pancasila Education learning using the Cooperative Learning model of the Team Games Tournament type in class IV of SDN 15 Ulu Gadut, Padang City. This type of research is Classroom Action Research (CAR) using qualitative and quantitative approaches. This research was conducted in two cycles, cycle I with two meetings and cycle II with one meeting. The subjects of the study were teachers (researchers) and students totaling 23 students consisting of 9 male students and 14 female students. The results of this study showed an increase: 1) The average implementation of the learning module in cycle I was 87.5% (B) increasing in cycle II to 95.83% (A). 2) The implementation of teacher activities in cycle I averaged 85.71% (C) increasing in cycle II to 96.42% (A). 3) The implementation of student activities in cycle I averaged 87.49% (B) increasing in cycle II to 96.42% (A). 4) The average student learning outcomes in cycle I were 75.37 (D) increasing to 89.07 (B) in cycle II.